Is a Newspaper's Companion Website a Competing Outlet Channel for the Print Version? - Ulrich Kaiser (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
This paper uses Granger noncausality tests to analyze if channel competition exists between the companion websites of 93 German newspapers observed between I/1998 and II/2005. It provides econometric evidence for significant negative effects of companion website tra?c on the print circulation of national newspapers and for significantly positive effects on local newspapers, at least for the period since I/2002.
Keywords: C32; C33; L11; 330; channel competition; Granger non-causality; panel data models; website visits; magazine circulation; Zeitung; Homepage; Internet; Vertriebsweg; Wettbewerb; Schätzung; Deutschland